Using Structured Expert Judgment to Assess Invasive Species Prevention: Asian Carp and the Mississippi—Great Lakes Hydrologic Connection - Wittmann, Marion E. (American Chemical Society, 2014)
[Image: see text] Recently, authors have theorized that invasive species prevention is more cost-effective than control in protecting ecosystem services. However, quantification of the effectiveness of prevention is rare because experiments at field scales are expensive or infeasible. We therefore used structured expert judgment to quantify the efficacy of 17 proposed strategies to prevent Asian carp invasion of the Laurentian Great Lakes via the hydrologic connection between the Mississippi and Great Lakes watersheds. Performance-weighted expert estimates indicated that hydrologic separation would prevent 99% (95,100; median, 5th and 95th percentiles) of Asian carp access, while electric and acoustic-bubble-strobe barriers would prevent 92% (85,95) and 92% (75,95), respectively. For all other strategies, estimated effectiveness was lower, with greater uncertainty. When potential invasions by other taxa are considered, the effectiveness of hydrologic separation increases relative to strategies that are effective primarily for fishes. These results could help guide invasive species management in many waterways globally.